De ondergang der Eerste Wareld - Bilderdijk, Willem, 1756-1831 (Salt Lake City, UT : Project Gutenberg, 2005)
"De ondergang der Eerste Wareld" by Willem Bilderdijk is an epic poem written during the early 19th century. The work explores themes of humanity's fall from grace, weaving together elements of myth, spirituality, and morality, centering around the biblical story of creation, sin, and the consequences that followed. It delves deeply into the intertwining of divine and human realms, portraying profound emotional struggles faced by its characters, particularly focusing on the lineage of Adam and the broader implications of their actions on civilization. At the start of the poem, the author introduces a preface that expresses a longing for the appreciation of heroic poetry amidst a time perceived as lacking poetic taste. The narrative begins with an invocation to the Muses and sets the stage for the underlining themes of loss, divine judgment, and the hope for redemption. It highlights the fall of man and the consequences of straying from God's commandments, with an emphasis on the deep emotional turmoil faced by key figures like Adam and Eve. The characters reflect upon the nature of existence and the struggle between good and evil, pledging to rise from the ruins of a fallen world while grappling with the realities of life shaped by sin and suffering. (This is an automatically generated summary.)
Release date is 2005-07-01
Produced by Jeroen Hellingman
Keywords: Dutch poetry